2003
DOI: 10.1097/01.asn.0000072743.97583.db
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Acute Effects of A1 Adenosine Receptor Activation on Na+/H+ Exchanger 3 in Opossum Kidney Cells

Abstract: Abstract. Regulation of renal apical Na ϩ /H ϩ exchanger 3 (NHE3) activity by adenosine has been suggested to contribute to acute control of mammalian Na ϩ homeostasis. The mechanism by which adenosine controls NHE3 activity in a renal cell line was examined. The adenosine analog, N 6 -cyclopentyladenosine (CPA) exerts a bimodal effect on NHE3: CPA concentrations Ͼ10 Ϫ8 M inactivate NHE3, whereas concentrations Ͻ10 Ϫ8 M stimulate NHE3 activity. Acute CPA-induced control of NHE3 was blocked by antagonists of A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
46
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 39 publications
15
46
0
Order By: Relevance
“…Interestingly, the binding of ouabain to Na ϩ -K ϩ -ATPase not only tethers PLC-␥ 1 and the inositol 1,4,5-trisphosphate receptor (IP 3 R) together to form a Ca 2ϩ -regulatory complex (54) but also stimulates the interaction of the NH 2 terminus of the endoplasmic reticulum-localized IP 3 R with the NH 2 terminus of the Na ϩ -K ϩ -ATPase ␣-subunit (55). These observations support the notion that ouabain-activated Na ϩ -K ϩ -ATPase signaling may also regulate NHE3 in the renal proximal tubule, since intracellular Ca 2ϩ has been shown to regulate NHE3 activity and trafficking (16,29).…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, the binding of ouabain to Na ϩ -K ϩ -ATPase not only tethers PLC-␥ 1 and the inositol 1,4,5-trisphosphate receptor (IP 3 R) together to form a Ca 2ϩ -regulatory complex (54) but also stimulates the interaction of the NH 2 terminus of the endoplasmic reticulum-localized IP 3 R with the NH 2 terminus of the Na ϩ -K ϩ -ATPase ␣-subunit (55). These observations support the notion that ouabain-activated Na ϩ -K ϩ -ATPase signaling may also regulate NHE3 in the renal proximal tubule, since intracellular Ca 2ϩ has been shown to regulate NHE3 activity and trafficking (16,29).…”
Section: Discussionsupporting
confidence: 85%
“…Notably, studies in opossum kidney cells indicated that activation of adenosine A 1 receptors exerts a bimodal effect on the Na ϩ -H ϩ exchanger NHE3, which is known to play a major role for Na ϩ reabsorption in proximal tubule (349): low concentrations (Ͻ10 Ϫ8 M) of the adenosine analog N 6 -cyclopentyladenosine (CPA) stimulated NHE3 and high concentrations (Ͼ10 Ϫ8 M) inactivated NHE3. Moreover, CPA-induced control of NHE3 was blocked by adenosine A 1 receptor antagonists (68). The inactivation of NHE3 by adenosine was suggested to involve calcineurin homologous protein-mediated regulation of NHE3 (67).…”
Section: A Proximal Tubulementioning
confidence: 97%
“…The intracellular signaling pathways that contribute to adenosine A 1 receptor-mediated increases in proximal tubular reabsorption are still under investigation but may include increases of intracellular Ca 2ϩ (68) and/or reductions of intracellular cAMP levels (174). Notably, studies in opossum kidney cells indicated that activation of adenosine A 1 receptors exerts a bimodal effect on the Na ϩ -H ϩ exchanger NHE3, which is known to play a major role for Na ϩ reabsorption in proximal tubule (349): low concentrations (Ͻ10 Ϫ8 M) of the adenosine analog N 6 -cyclopentyladenosine (CPA) stimulated NHE3 and high concentrations (Ͼ10 Ϫ8 M) inactivated NHE3.…”
Section: A Proximal Tubulementioning
confidence: 99%
“…In accordance, in vitro studies in the proximal tubule showed that activation of A 1 receptor can stimulate transport of fluid, HCO 3 Ϫ as well as Na ϩ -glucose and Na ϩ -phosphate symport (Coulson et al, 1991;Takeda et al, 1993;Cai et al, 1994Cai et al, , 1995. The intracellular signaling pathways that contribute to these changes in tubular transport are still under investigation but may include reductions of intracellular cAMP levels (Kost et al, 2000), increases of intracellular Ca 2ϩ (Di Sole et al, 2003), and calcineurin homologous proArticle, publication date, and citation information can be found at http://jpet.aspetjournals.org. doi:10.1124/jpet.104.080432.…”
mentioning
confidence: 88%